2017
DOI: 10.15376/biores.12.4.7255-7267
|View full text |Cite
|
Sign up to set email alerts
|

Anti-bacterial and anti-mold efficiency of ZnO nanoparticles present in melamine-laminated surfaces of particleboards

Abstract: Lamination is one of the most widely used techniques for the surface treatment of wood-based composites such as particleboards, fiberboards, etc. It is usually carried out using décor papers impregnated with amino thermosetting resins, mostly melamine-formaldehyde, urea-formaldehyde, or their mixture. Conventional laminates with non-bioactive surfaces are not able to reduce or stop microbial growth when contaminated with organic substances. In this work, zinc oxide (ZnO) nanoparticles were applied into their s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The measurement of formaldehyde in air was carried out on a PU cross-linked hybrid P(AAm/DA)-Ag/MgO hydrogel coating with a multi-scale channel structure. The amount of formaldehyde in air was measured according to the protocol mentioned in the publication from Bourguignon et al 50 The volume of the vessel was 600 cm 3 . A formaldehyde release bottle containing 5 mL of formaldehyde aqueous solution (0.2 mg mL −1 ) and a formaldehyde receiving bottle containing 5 mL of water were placed in the vessel.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The measurement of formaldehyde in air was carried out on a PU cross-linked hybrid P(AAm/DA)-Ag/MgO hydrogel coating with a multi-scale channel structure. The amount of formaldehyde in air was measured according to the protocol mentioned in the publication from Bourguignon et al 50 The volume of the vessel was 600 cm 3 . A formaldehyde release bottle containing 5 mL of formaldehyde aqueous solution (0.2 mg mL −1 ) and a formaldehyde receiving bottle containing 5 mL of water were placed in the vessel.…”
Section: ■ Introductionmentioning
confidence: 99%
“…During the fabrication of cars, a huge number of chemical products and agents are applied, such as plastic interiors, adhesive agents, and cleaning detergents. Among various volatile organic compounds, formaldehyde is considered to be the main factor of air pollution in car. Due to the high reactivity of formaldehyde, it can undergo the nucleophilic addition reaction with hydroxyl, sulfhydryl, and amino groups in human cells and the enzyme system. It can further denature proteins and seriously endanger human health, leading to problems such as eye irritation, headache, leukemia, etc .…”
Section: Introductionmentioning
confidence: 99%
“…Most recent research has shown that the production of customer-specific products stands out. Researchers are now working for the discovery of innovative products that are more resistant to scratch, dirt, fungi, biological pests, and more considerate of the environment and human health while revealing ways to produce higher quality products at lower costs (Kim and Kim, 2006;Kandelbauer et al, 2010;Badila et al, 2014;Kohlmayr et al, 2014;Nosál and Reinprecht, 2017). Thus, effective analysis processes are needed to produce quality products that can meet user demands, optimize the parameters affecting the process, and provide them on short notice.…”
Section: Introduction 1 Uvodmentioning
confidence: 99%
“…Inorganic additives include metals such as silver, copper, and zinc in different forms (salt; nano-sized), TiO 2 , or others. It was reported that the addition of nanoparticles to the surface of materials leads to improved antimicrobial resistance [18,19]. In order to form particles and avoid clustering, it is necessary to stabilize them in a suitable matrix, which will ensure a homogeneous structure and their uniform distribution [20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%